Protein Bioinformatics Infrastructure for the Integration and Analysis of Multiple High-Throughput "omics" Data. (22nd February 2010) - Chen, Chuming; McGarvey, Peter B.; Huang, Hongzhan; Wu, Cathy H.
Abstract : High-throughput "omics" technologies bring new opportunities for biological and biomedical researchers to ask complex questions and gain new scientific insights. However, the voluminous, complex, and context-dependent data being maintained in heterogeneous and distributed environments plus the lack of well-defined data standard and standardized nomenclature imposes a major challenge which requires advanced computational methods and bioinformatics infrastructures for integration, mining, visualization, and comparative analysis to facilitate data-driven hypothesis generation and biological knowledge discovery. In this paper, we present the challenges in high-throughput "omics" data integration and analysis, introduce a protein-centric approach for systems integration of large and heterogeneous high-throughput "omics" data including microarray, mass spectrometry, protein sequence, protein structure, and protein interaction data, and use scientific case study to illustrate how one can use varied "omics" data from different laboratories to make useful connections that could lead to new biological knowledge.